Integrated working with children and young people : supporting development from birth to nineteen - Edmond, Nadia; Price, Mark (Sage Publications, 2012)
This interdisciplinary core textbook look at learning and development from birth to nineteen, and provides an accessible introduction to the common areas of study across the many roles supporting learning and development in the young people's workforce. There is coverage of common themes and issues, and theory is closely integrating with practice throughout. -- BACK COVER.